Fault detection for discrete time-delay networked systems with round-robin protocol in finite-frequency domain - Ju, Yamei; Wei, Guoliang; Ding, Derui; Zhang, Sunjie (International journal of systems science, 2019)
The paper considers the fault detection problem over finite-frequency domain for a class of discrete time-delayed networked systems subject to round-robin protocol. This protocol is a periodic one to schedule the information transmitted via a shared communication network with an intent to prevent the data from collisions. In this scenario, the error dynamics can be regarded as a periodic protocol-induced system. The aim of the problem addressed is to design a fault detection filter that (1) the sensitivity of the residual to the fault is enhanced by means of a maximised index and (2) the effect from the exogenous disturbances on the residual is decreased with considering a minimised index. By resorting to a Lyapunov function, an improved version of generalised Kalman-Yakubovich-Popov lemma (GKYP) is first developed for protocol-induced periodic system. Then, in light of such a lemma, sufficient conditions are derived to guarantee both the fault sensitivity and the disturbance attenuation capability by solving a set of matrix inequalities. Finally, the usefulness of the presented fault detection algorithm is utilised via a numerical simulation.